Effet de l’alimentation sur les paramètres hématologiques chez les patients atteints de cancer de poumon suivis au niveau du CHU d’Oran « Service d’oncologie » - MANSOURI, MOUNIRA; BELAIDI, WIDAD (My University, 2024)
Lung cancer remains the leading cause of cancer-related deaths worldwide, showing the highest mortality rates among both sexes. Our study aims to evaluate the impact of consuming certain spices (turmeric, star anise, cloves) on the hematological parameters of patients with lung cancer. This study was conducted by comparing an experimental group receiving specific spices, tested from the start of the treatment, and a control group that did not receive this specific intervention, aged between 43 and 72 years and hospitalized at the Oran University Hospital "Plateau" from February 4, 2024, to May 31, 2024. Our results reveal that the age group between 60 to 69 is the majority class with a percentage of 54% between the two groups. A majority of the experimental group (85%) have an optimal weight compared to 38% of the controls. The vast majority of experimental cases (85%) consumed tobacco before treatment, while a minority (15%) consumed alcohol. Tobacco and alcohol consumption significantly decreased during treatment in both groups. Medical histories such as COPD (chronic obstructive pulmonary disease) are more frequent in the experimental group (54%) compared to the control group (38%). There is no significant difference between the hematological parameters in the two groups before chemotherapy except for the platelet count (PLT). The experimental group has a median PLT around 250.103/mm3, while the control group shows a similar median around 180.103/mm3. After the first chemotherapy, the experimental group shows a median PLT around 300.103/mm3, higher than that of the control group (240.103/mm3). In contrast, other parameters (red blood cells, white blood cells, hematocrit, mean corpuscular volume (MCV), lymphocytes (LYM), granulocytes, mean corpuscular hemoglobin content (MCHC), and mean corpuscular hemoglobin concentration (MCHC)) were similar in both groups. After the second chemotherapy, the platelet count (PLT) remained higher for the experimental group (250.103/mm3 vs. 200.103/mm3 for the control), while the lymphocyte count was better for the control group (34% vs. 27% for the experimental group). Correlation matrix results show complex interactions between various blood parameters, and these interactions may be altered in patients with lung cancer. Our results are consistent with the literature suggesting that incorporating these spices into the diet could positively impact hematological parameters, potentially offering protective effects against lung cancer, particularly non-small cell adenocarcinoma.
Keywords: Cancer; spices; chemotherapy; blood parameters; diet